2006
DOI: 10.1021/cb600276q
|View full text |Cite|
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Activity of a Potent Smac Mimetic That Sensitizes Cancer Cells to Apoptosis by Antagonizing IAPs

Abstract: Designed second mitochondrial activator of caspases (Smac) mimetics based on an accessible [7,5]-bicyclic scaffold bind to and antagonize protein interactions involving the inhibitor of apoptosis (IAP) proteins, X-chromosome-linked IAP (XIAP), melanoma IAP (ML-IAP), and c-IAPs 1 and 2 (cIAP1 and cIAP2). The design rationale is based on a combination of phage-panning data, peptide binding studies, and a survey of potential isosteres. The synthesis of two scaffolds is described. These compounds bind the XIAP-bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
174
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(179 citation statements)
references
References 43 publications
4
174
1
Order By: Relevance
“…Notably, the role of cIAP1 and 2 as negative regulators of stimulus-independent classical and alternative NF-B signaling (11,12) was uncovered in studies using small-molecule IAP antagonist compounds. These compounds were designed to mimic the interaction between XIAP and its antagonist Smac (second mitochondria-derived activator of caspases) and show great promise for the treatment of cancer (26). Smac-mimetics were intended to de-repress XIAP-mediated inhibition of apoptosis in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the role of cIAP1 and 2 as negative regulators of stimulus-independent classical and alternative NF-B signaling (11,12) was uncovered in studies using small-molecule IAP antagonist compounds. These compounds were designed to mimic the interaction between XIAP and its antagonist Smac (second mitochondria-derived activator of caspases) and show great promise for the treatment of cancer (26). Smac-mimetics were intended to de-repress XIAP-mediated inhibition of apoptosis in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with Smac, Smac mimetic could cross the cell membrane and bind efficiently to its target proteins (65). It was shown that Smac mimetic possessed the ability of activating caspase-3 and caspase-7, reducing cell viability of MDA-MB-231 breast cancer cells and A2058 melanoma cells, and enhancing doxorubicininduced apoptosis (66). Together, the development of small molecules is offering not only prospects for individualized treatment but also a valuable therapeutic window to limit unwanted side effects (67,68).…”
Section: Targeting Livin By Blocking Protein Functionmentioning
confidence: 99%
“…By binding to XIAP and cIAPs, Smac can release the inhibition of caspase or lead to the degradation of cIAPs, which in turn activates the apoptosis process in cells (26,27). Therefore, regarding the potency of Smac to revert the antiapoptotic process of cancer cells, several Smac mimetics have been designed and synthesized as antitumor drugs in recent years (28)(29)(30)(31). These compounds can induce cIAP1/2 degradation and prevent XIAP from binding to caspases, which induce the apoptosis of tumor cells with little effect on normal cells (27,32).…”
Section: Introductionmentioning
confidence: 99%